2016
DOI: 10.1038/srep37089
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bovine pericardial extracellular matrix scaffold niche on seeded human mesenchymal stem cell function

Abstract: Numerous studies have focused on generation of unfixed bovine pericardium (BP) extracellular matrix (ECM) for clinical application. However, the extent to which maintenance of native ECM niche is capable of directing behavior of repopulating cells remains relatively unexplored. By exploiting the sidedness of BP scaffolds (i.e., serous or fibrous surface), this study aims to determine the effect of ECM niche preservation on cellular repopulation using different scaffold generation methods. BP underwent either s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 58 publications
0
34
1
Order By: Relevance
“…Prior to the initiation of the biocompatibility assays of the BPs, it is necessary to be aware of tissue cytotoxicity after the decellularization process. In this context, a residual cytotoxic effect, attributed to the strong anionic detergent potential, was previously demonstrated in SDS‐treated tissues even after 7 days of washing . High levels of detergent residues are related to loss of tensile strength and to increased elastin fiber proteolysis, which may lead to subsequent structural degeneration .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Prior to the initiation of the biocompatibility assays of the BPs, it is necessary to be aware of tissue cytotoxicity after the decellularization process. In this context, a residual cytotoxic effect, attributed to the strong anionic detergent potential, was previously demonstrated in SDS‐treated tissues even after 7 days of washing . High levels of detergent residues are related to loss of tensile strength and to increased elastin fiber proteolysis, which may lead to subsequent structural degeneration .…”
Section: Discussionmentioning
confidence: 91%
“…The use of hASCs for tissue repopulation is desirable mainly due to their immunomodulatory and pro‐regenerative properties . In addition, hASCs can be obtained from the patient without an invasive removal procedure, allowing a humanized and autologous transplant.…”
Section: Discussionmentioning
confidence: 99%
“…This results in persistence of both known (e.g., MHC I) and unknown (i.e., 70% residual antigenicity remaining) lipophilic antigens [3,13,32]. Furthermore, studies have shown SDS to severely denature vital ECM proteins and be toxic to repopulating cells, stimulating recipient innate immune mediated foreign body response [3,10,13,3335]. Conversely, zwitterionic detergents (e.g., sulfobetaines) are powerful protein solubilizers due to their hydrophilic head and hydrophobic tail [23,24,36].…”
Section: Discussionmentioning
confidence: 99%
“…To ameliorate stem cell engraftment, several approaches have been investigated including genetic manipulation of cells to increase homing and survival as well as tissue engineering techniques involving preparation of scaffolds . Scaffolds that are derived from decellularized natural tissues appear to be appropriate and efficient as they possess the essential natural tunnels for vessels and nerves as well as the porosity to nest‐specific cell lineage.…”
Section: Discussionmentioning
confidence: 99%
“…15 To ameliorate stem cell engraftment, several approaches have been investigated including genetic manipulation of cells to increase homing and survival as well as tissue engineering techniques involving preparation of scaffolds. 5,[16][17][18][19] Scaffolds that are derived from decellularized natural tissues appear to be appropriate and efficient as they possess the essential natural tunnels for vessels and nerves as well as the porosity to nest-specific cell lineage. An appropriate approach for decellularization of scaffolds would preserve the extracellular matrices' integrity and structural features resulting in better signaling and cell homage, while at the same time omitting cells and reducing immunologic reactions.…”
Section: Discussionmentioning
confidence: 99%